(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Although there are several methods to detect Helicobacter pylori infection, there is no simple validated test to quantify the density of infection, which is believed to play a major role in the pathogenesis of H. pylori-associated Gastritis and serum Ferritin level. Objective: The aim of this study was to assess the association of low serum Ferritin level with the intensity of H. pylori infection. Patients and Methods: Sixty four patients mean age of 34 years (14-66 years) who underwent upper gastrointestinal endoscopy because of gastrointestinal complaints, were studied. Patients were grouped as H. pylori positive group, n=47and H. pylori negative group, n=17. A number of both invasive and non-invasive diagnostic tests were used for the diagnosis of H. pylori infection (Ultra Rapid Urease Test (URUT), slide impression smear test and H.pylori IgG ELISA Test). Fasting serum Ferritin were determined using VIDAS Ferritin (Enzyme Linked Fluorescent Assay). Results: Forty seven of the 64(73%) patients were H.pylori positive group. patients were classified according to the age group and gender. The rates of the H.pylori infection were higher in female age group 21-30 years. A total 16 of the 47 (34%) infected patients showed low serum Ferritin values with high rate in female with age group 21-30years. Twenty eight of the 47(60%) patient biopsies showed positive microscopic examination with slide impression smear test .Twenty seven of the 47(57%) infected patients showed seropositive results to anti-H.pylori IgG antibody and also positive with URUT,10 individuals of this group showed low serum Ferritin values. While ten of the47 (21%) infected patients showed seronegative results to anti-H.pylori IgG antibody but positive with URUT,5 individuals of this group showed low serum Ferritin values. Conclusion: The possible relationship between mucosal H.pylori loads with low serum Ferritin level. Keywords: Helicobacter pylori infection, serum Ferritin, anti-H.pylori IgG antibody ELISA test, Ultra Rapid Urease, Enzyme Linked Fluorescent Assay